Reduced ex vivo release of pro-inflammatory cytokines and elevated plasma interleukin-6 are inflammatory signatures of post-stroke delirium - Kowalska, Katarzyna (J Neuroinflammation, 2018)
BACKGROUND: Experimental studies suggest that systemic inflammation contributes to the pathophysiology of delirium. The aim of our study was to determine blood-derived inflammatory signatures of post-stroke delirium. METHODS: We included 144 ischemic stroke patients. We assessed delirium on a daily basis during the first 7 days of hospitalization. Venous blood was collected at day 3 after the onset of stroke and stimulated ex vivo with lipopolysaccharide (LPS). We measured LPS-induced cytokine concentration (TNFα, IP-10, IL-1β, IL-6, IL-8, IL-10, and IL-12p70) as well as plasma levels of IL-6 and TNFα. RESULTS: Delirium was diagnosed in 21.5% of patients. After correction for monocyte count, patients with delirium had reduced LPS-induced TNFα, IP-10, IL-1β, IL-6, and IL-12 release. The plasma IL-6 level was higher in delirious patients compared to patients without delirium. After adjusting for stroke severity and infections, higher ex vivo TNFα (OR 0.29, 95%CI 0.11–0.72, P = 0.01), IP-10 (OR 0.25, 95%CI 0.08–0.73, P = 0.01), IL-1β (OR 0.42, 95%CI 0.20–0.89, P = 0.02), and IL-12 (OR 0.07, 95%CI 0.01–0.70, P = 0.02) release was associated with the reduced risk of delirium. In multivariate analysis, the higher plasma IL-6 was associated with the increased risk of delirium (OR 1.61, 95%CI 1.00–2.58, P = 0.04). CONCLUSIONS: Reduced ex vivo release of pro-inflammatory cytokines after LPS stimulation and the elevated plasma IL-6 are signatures of post-stroke delirium.